PENGARUH COVID-19 TERHADAP RETURN SAHAM PADA PERUSAHAAN CONSUMER GOODS - Rosalee, Christine; Suhendah, Rousilita (Jurnal Paradigma Akuntansi, 2023)
This study aims to determine the effect of Covid-19, PSBB, market capitalization, and trading volume on stock returns in consumer goods companies listed on the Indonesia Stock Exchange (IDX) starting on March 2, 2020 until December 31, 2020. This study using 50 samples and 10900 data on consumer goods companies that have been selected using the purposive sampling method. This study uses secondary data and the data is managed using Microsoft Excel and Eviews version 10 software. The results show that the growth of positive Covid-19 cases has a negative effect on stock returns, the PSBB policy has no effect on stock returns, and market capitalization and trading volume have a positive effect. to stock returns. The implication of this research is the need for companies to increase awareness of situations that affect stock returns.